Less human, more to blame: Animalizing poor people increases blame and decreases support for wealth redistribution. (June 2020) - Sainz, Mario; Martínez, Rocío; Sutton, Robbie M.; Rodríguez-Bailón, Rosa; Moya, Miguel
Increasing economic inequality adversely affects groups with low socioeconomic status (low-SES). However, many people are opposed to wealth redistribution policies. In this context, we examined whether dehumanization of low-SES groups has a role in this opposition. In the first study ( N = 303), opposition to wealth redistribution was related to denying human uniqueness (e.g., intelligence and rationality) and having negative attitudes toward low-SES groups, more than denying human nature (e.g., emotionality and capacity to suffer) to low-SES groups. Mediation analyses indicated that this effect occurred via blaming low-SES groups for their plight, after controlling for participants' SES and negative attitudes towards low-SES groups. In the second study ( N = 220), manipulating the human uniqueness of a fictitious low-SES group affected support for wealth redistribution measures through blame. These results indicate that animalizing low-SES groups reduces support for wealth redistribution via blaming low-SES groups for their situation.